Anywhere On-Keyboard Password technique - Abdul Ameer, Dalia Abdul Hadi; AL-Absi, Ahmed Abdulhakim; Mohammed, Abu Obaydah; Monzer Habbal, Adib M.; Hassan, Suhaidi (2010)
Traditional authentication technique generally requires an id and password to verify the identity of user.By nature, user is looking for a password that is easy to remember and secured from any attack.However, remembering many complicated passwords, especially when user has different accounts, is not an easy task.Moreover,Traditional technique is still vulnerable to attack such as hidden camera.To overcome these drawbacks, we propose a new password authentication technique called “Anywhere On-Keyboard Password (AOKP)”.The experiment results show that 40% of the spies succeed to catch the password shape but all of them fail to detect the number of the strokes.Therefore, the proposed technique provides more secure and memorable authentication method through changing password from text to mix shape and number of strokes. In addition, it has high level of scalability and simplicity though the freedom of writing the password anywhere on keyboard, password length and language independent.